- #1

- 21

- 0

## Main Question or Discussion Point

I'm doing my first paper review and an equation is holding me up. I can't tell if I'm just missing something silly or if the author made a mistake.

Given that:

[tex]\sum_{n=1}^{N}s_{n} = 1[/tex]

The author says that:

[tex]\sum_{n=1}^{N}(s_{n} - \frac{1}{N})^{2} = \sum_{n=1}^{N}s_{n}^{2} - \frac{1}{N}[/tex]

I seem to be having some trouble getting this to work. Am I just missing something? Or is this the author's mistake? Thanks!

Given that:

[tex]\sum_{n=1}^{N}s_{n} = 1[/tex]

The author says that:

[tex]\sum_{n=1}^{N}(s_{n} - \frac{1}{N})^{2} = \sum_{n=1}^{N}s_{n}^{2} - \frac{1}{N}[/tex]

I seem to be having some trouble getting this to work. Am I just missing something? Or is this the author's mistake? Thanks!